Recobrimento e desverdecimento em frutos de laranjeira “valência delta” armazenados sob diferentes temperaturas. - Pereira, Gerlândia da Silva (2012)
The fruit of the cultivar 'Valencia' is a sweet orange of excellent quality, both for production of juice and for consumption in natura. The study aimed to evaluate the quality and conservation, the effect of the use of carnauba based wax (ARUÁ TROPICAL®) and/or degreening in the fruits of orange 'Valencia Delta' produced in the area of semi-arid climate under different storage conditions. The influence of coating on the fruit and its effects was appraised on physical and physical-chemical properties. The oranges of the cultivar 'Valencia Delta', produced at the pole Baixo Jaguaribe, state of Ceará, were coated with carnauba based wax and stored at room temperature and refrigerated, for a period of 28 days. In a second experiment, the fruits were degreened with exogenous ethylene and, after degreening, coated with carnauba based wax. Simultaneously, two experiments were conducted: in first, the fruits were stored under refrigerated conditions by 35 days and submitted to physical and physical -chemical analysis. For the second experiment, among the refrigerated fruits were removed samples for the ambient storage (3 days at 24° C and 40 % RH). The coated fruits showed the lowest mass loss at the end of the experiment, high yield of juice and soluble solids level, high ratio SS/TA and the bioactive compounds showed increase during the storage period. The degreened fruits decreased in bioactive compounds during storage and showed low level of soluble solids. The application of degreening promoted change in the color of the peel, making them yellow fruit, and the use of coating on oranges 'Valencia Delta' was effective because it reduced the loss of weight, enhanced the brightness of the flavedo and maintained the visual quality of the fruits during the storage period. The refrigerated storage associated with the use of coating was affective for the external characteristics of fruits and preserved the indicator parameters of the internal quality.